Optimizing Financial and Marketing Strategies for Sustainable Growth in Indian Aquaculture Industry - Betala, Avinash (Digital Repository of Theses, 2025)
India’s aquaculture industry, the world’s second largest, plays a vital role in food security, employment, and economic growth. Despite its significance, the sector faces challenges in financial sustainability, marketing effectiveness, and socio-economic and environmental impacts. This dissertation aims to optimize financial and marketing strategies to promote sustainable growth in the Indian aquaculture industry. The research addresses three key questions: (1) identifying common funding channels and their effects on operational costs and profitability; (2) examining the impact of various marketing channels, pricing strategies, and supply chain management on market reach and profitability; and (3) exploring the socio-economic and environmental costs associated with aquaculture for sustainable policy development. A qualitative methodology was adopted, involving semi-structured interviews with 45 stakeholders across three major aquaculture regions of India: West Godavari, Hooghly, and Kollam. Participants included aquaculture farmers, industry experts, financial analysts, marketing professionals, supply chain managers, environmental scientists, local government officials, and community members. Findings indicate that the primary funding channels are private investments (38%), government grants (33%), and bank loans (29%). Private investments foster innovation but may pressure profitability due to investor expectations. Government grants alleviate initial capital burdens but encounter bureaucratic delays affecting operational efficiency. Bank loans provide necessary capital but impose high-interest rates and strict repayment terms, impacting financial sustainability. In terms of marketing strategies, online platforms and export markets are effective in expanding market reach and enhancing profitability. A transition from competitive pricing to value-based pricing allows producers to align prices with perceived quality, improving profit margins. Supply chain optimization—through logistics efficiency and strict quality control—is essential for timely deliveries and customer retention. The socio-economic analysis reveals that aquaculture contributes to job creation and income improvement but raises environmental concerns such as biodiversity loss and water pollution due to intensive farming practices. Community Supported Aquaculture (CSA) initiatives emerge as promising approaches to engage stakeholders in sustainable practices and equitable resource distribution. To ensure long-term viability, the study recommends diversifying funding sources, expediting grant disbursement, leveraging digital marketing, refining pricing strategies, enhancing supply chain efficiency, and implementing sustainable farming practices. These insights provide a strategic foundation for balancing economic growth with environmental stewardship in India's aquaculture sector.